Influence of the charge materials on the quality of cast wheel rims made from AK7 alloy. (July 2020) - Cherepanov, A I; Kukartsev, V A; Kukartsev, V V; Dzhioeva, N N; Bets, Yu S; Makarchuk, I Yu
Abstract: The widespread use of aluminum and alloys based on it in mechanical engineering is determined by high values of specific strength, increased corrosion resistance, as well as the ability to damp vibrations and high energy absorption. These indicators are especially important in the production of cars, as these alloys can reduce product weight and, as a result, the amount of fuel consumed. Reduced weight of cars can reduce harmful emissions into the environment and reduce the pressure on the road surface. Currently, AK7 cast aluminum alloy is the standard alloy for making rims. To obtain an alloy with the necessary properties, it is necessary to take into account the quality of the used charge materials. First of all, this applies to foundry alloys, which are used for alloying and alloy modification. In the study, we studied AlSi10 pig foundry alloy and AlTi5B1 foundry alloy rod.